Analysis of the suitability of natural components for ecotourism planning in Haditha District using GIS and RS techniques - Al-Shaabani, Prof. Dr. Mohamed Moussa Hammadi Al-Shaabani; Al-Saffar., Asst.Prod.Dr. Bahri Salem Fattah Al-Saffar.; Abdul-Ani, Salah Othman Abdul-Ani (Sulaimani Journal for Humanities, 2025)
This study aims to analyze the suitability of natural components in the Haditha District for sustainable ecotourism planning by employing Geographic Information Systems (GIS) and Remote Sensing (RS) to develop a comprehensive spatial model that assesses the capacity of land units to accommodate ecotourism activities. The analysis focused on several key natural factors, including geological formations, topographic features, geomorphology, slope, climate, water resources, and vegetation cover. Each factor was assigned a relative weight based on its impact on ecotourism, and the layers were integrated within the GIS environment to generate suitability maps. The results revealed that approximately 67% of the district's area falls within the moderate and high suitability categories, indicating a substantial spatial potential for sustainable tourism development. Karstic areas, the banks of the Euphrates River, and Haditha Lake emerged as major environmental attractions. The study also highlighted the critical role of soil and vegetation in supporting biodiversity and promoting educational and research-based tourism. It recommends the continuous use of spatial analysis tools to update environmental databases and guide tourism investments in alignment with principles of sustainability and balanced environmental planning.
Keywords: This study aims to analyze the suitability of natural components in the Haditha District for sustainable ecotourism planning by employing Geographic Information Systems (GIS) and Remote Sensing (RS) to develop a comprehensive spatial model that assesses the capacity of land units to accommodate ecotourism activities The analysis focused on several key natural factors; including geological formations; topographic features; geomorphology; slope; climate; water resources; and vegetation cover Each factor was assigned a relative weight based on its impact on ecotourism; and the layers were integrated within the GIS environment to generate suitability maps The results revealed that approximately 67 of the districts area falls within the moderate and high suitability categories; indicating a substantial spatial potential for sustainable tourism development Karstic areas; the banks of the Euphrates River; and Haditha Lake emerged as major environmental attractions The study also highlighted the critical role of soil and vegetation in supporting biodiversity and promoting educational and researchbased tourism It recommends the continuous use of spatial analysis tools to update environmental databases and guide tourism investments in alignment with principles of sustainability and balanced environmental planning